PENGARUH MEDIA SOSIAL, LITERASI KEUANGAN, RISIKO, IMBAL HASIL, DAN RELIGIUSITAS TERHADAP MINAT BERINVESTASI SUKUK GENERASI Z DI JAKARTA - Aliyah Zahrah Fadhilah Ladamay (2021)
This research is a type of quantitative research with the aim of knowing the effect of social media, financial literacy, risk, returns, and religiosity on interest in investing in Generation Z sukuk in Jakarta. The sampling technique in this study used a non-probability sampling technique with purposive sampling type. Data collection techniques through questionnaires usingscale measurements Likert. In this study using a quantitative descriptive method with multiple linear regression analysis test. Supported by validity and reliability tests, classical assumption test, and hypothesis testing consisting of F test, T test, and the coefficient of determination test (R2). Assisted by software SPSSversion 25. The results contained in this study are the variables of social media, financial literacy, risk, returns, and religiosity simultaneously or simultaneously have a significant effect, while partially social media variables, risk, and religiosity have an effect, financial literacy and returns do not have a significant effect partially. The recommendations given are to add variables outside of this research for further research, to expand the reach of the population, regulators can take advantage of influential factors, and this research is expected to be a reference for further related research.